Depletion of the Squalene Synthase (ERG9) Gene Does Not Impair Growth of Candida glabrata in Mice - Nakayama, Hironobu (American Society for Microbiology, 2000)
Squalene synthase (farnesyl-diphosphate farnesyltransferase, EC 2.5.1.21) is the first committed enzyme of the sterol biosynthesis pathway. Inhibitors of this enzyme have been intensively studied as potential antifungal agents. To assess the effect of deactivating squalene synthase on the growth of fungi in mice, we isolated the squalene synthase (ERG9) gene from the pathogenic fungus Candida glabrata and generated strains in which the CgERG9 gene was under the control of the tetracycline-regulatable promoter. Depletion of the ERG9 gene by doxycycline (DOX), a derivative of tetracycline, decreased the cell viability in laboratory media, whereas it did not affect cell growth in mice at all. The growth defect caused by DOX in laboratory media was suppressed by the addition of serum. Analyses of the sterol composition of the restored cells in serum-containing media suggest that the defect of ergosterol biosynthesis can be complemented by the incorporation of exogenous cholesterol into the cells. Thus, deactivation of squalene synthase did not affect fungal growth in mice, presumably because the cells were able to incorporate cholesterol from the serum. These results showed that squalene synthase could not be a suitable target of antifungals for the treatment of C. glabrata infection.